Pharmacological treatment in dentistry. How does it affects patient's safety? - Karaben, Viviana E. (2022)
Patient safety is a quality dimension in health care, because there is a certain degree of danger in each step of the process; focusing on the use of medicines, the most harmful problems are related to errors in the selection of medicines and their correlation with the diagnosis and in the unjustified use of them. The objective of this study was to analyze drug prescription situations in relation to patient safety. It is a prospective, observational and descriptive study; of a sample made up of all the prescriptions received during 12 continuous months, prescribed by dentists for oral pathologies, from a social service institute, in the city of Corrientes, Argentina. The prescription situations were analyzed into adequate and inadequate, and the latter were subdivided into: a) excessive prescription or undermedication and b) inappropriate prescription in relation to the indicated medication or dose, with the diagnosis. A quantitative analysis of the prescribed drugs was performed with descriptive statistics and a qualitative analysis through quality parameters such as the number of active ingredients that the drug contains and the "potential therapeutic intrinsic value" (PTIV). Results: 518 prescriptions were prescribed by dentists for oral pathologies, 20% presented situations of unsafe use, 17 prescriptions with excessive prescriptions or submedication and 86 prescriptions with an inappropriate relationship between the medication and the diagnosis. In conclusion, we have detected prescriptions with a high potential to produce adverse effects, as well as situations of lack of knowledge about therapeutic indications, with unnecessary use of antibiotics.